The Influence of One Door Integrated Service (PTSP) Factors on Community Satisfaction at the Office of the Ministry of Religion, Mojokerto District - Apri Wigatiningrum; Sundjoto Sundjoto; Sri Rahayu (CV. Rayyan Dwi Bharata, 2024)
The efficiency and effectiveness of public bodies has a direct effect on public satisfaction. Service quality is the main factor in community satisfaction. People's happiness is influenced by public services. The public has the right to receive quality services that meet the principles and objectives of service delivery. This research is explanatory quantitative research. The research was conducted by the Mojokerto Regency Ministry of Religion Office. This research investigates how the quality and effectiveness of services influence people's satisfaction. This research examines physical evidence, income, responsiveness, assurance, empathy, service effectiveness and community satisfaction. This research took a sample of 100 people. Data was obtained using a direct survey of respondents. Data analysis includes descriptive analysis, classical assumption test, multiple linear regression analysis, and t test using SPSS for Windows. The reliability, responsiveness, guarantee and effectiveness of the services of the Ministry of Religion of Mojokerto Regency statistically influence community satisfaction. Empathy does not affect people's satisfaction.